LEARNING INDONESIAN EVALUATION USING COOPERATIVE LEARNING MODEL JIGSAW TYPE THROUGH LESSON STUDY FOR LEARNING COMMUNITY - Yeni Rostikawati; Wikanengsih Wikanengsih (IKIP Siliwangi, 2018)
The problem found in the evaluation course is when developing the student test instrument is difficult to understand in preparing the test tool based on cognitive level that must be adjusted with the indicator, as well as in preparing the skill test. Their difficulty lies in the preparation of rubrics as the translation of learning objectives in the skill domain. In addition, arranging non-test tools such as observation sheets, interview guides, and questionnaires also experienced some obstacles. On the basis of that, efforts to improve the ability of students in the course of Learning Evaluation, especially in preparing test kits and non-test through jigsaw type cooperative learning model. The purpose of this research are: 1) describe the implementation of teaching Indonesian Language Evaluation Course using jigsaw type cooperative learning model; 2) to describe the student's response in the process of teaching implementation. The course of Indonesian Language Evaluation uses cooperative learning model of jigsaw type: and 3) describes the student's ability in preparing the evaluation tool of test and non-test after implementing the learning using jigsaw type cooperative learning model. The results of the implementation of the lesson study of Evaluation learning using jigsaw type cooperative learning model through Lesson Study for Learning Community can improve the collaborative, communication, critical thinking, and creative ability of the students. Therefore, the results of this study can be used as a reference for teachers to enrich references on learning models that can be used in the learning process.